Functional domains of the AraC protein. - Bustos, S A (1993)
The AraC protein, which regulates the L-arabinose operons in Escherichia coli, was dissected into two domains that function in chimeric proteins. One provides a dimerization capability and binds the ligand arabinose, and the other provides a site-specific DNA-binding capability and activates transcription. In vivo and in vitro experiments showed that a fusion protein consisting of the N-terminal half of the AraC protein and the DNA-binding domain of the LexA repressor dimerizes, binds well to a LexA operator, and represses expression of a LexA operator-beta-galactosidase fusion gene in an arabinose-responsive manner. In vivo and in vitro experiments also showed that a fusion protein consisting of the C-terminal half of the AraC protein and the leucine zipper dimerization domain from the C/EBP transcriptional activator binds to araI and activates transcription from a PBAD promoter-beta-galactosidase fusion gene. Dimerization was necessary for occupancy and activation of the wild-type AraC binding site.